2013
DOI: 10.2147/hiv.s46364
|View full text |Cite
|
Sign up to set email alerts
|

Serum selenium and skin diseases among Nigerians with human immunodeficiency virus/acquired immune deficiency syndrome

Abstract: BackgroundThe role of selenium as an antioxidant micronutrient has garnered the unprecedented focus of researchers in recent times. No clinical study has related serum selenium concentration to skin diseases in human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) patients.MethodsIn this study, 134 newly diagnosed HIV patients that satisfied the inclusion criteria were included. Skin diseases were clinically diagnosed and fasting venous blood was taken for assessment of serum selenium us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Like most previous pediatric studies which found rarely or no cases of tumor dermatosis such as Kaposi's disease we have not observed such cases. This observation may also be related to the short duration of our study which did not allow us to receive cases of infantile Kaposi's disease [5,9,19].…”
Section: Immunologic and Clinical Characteristicsmentioning
confidence: 96%
See 2 more Smart Citations
“…Like most previous pediatric studies which found rarely or no cases of tumor dermatosis such as Kaposi's disease we have not observed such cases. This observation may also be related to the short duration of our study which did not allow us to receive cases of infantile Kaposi's disease [5,9,19].…”
Section: Immunologic and Clinical Characteristicsmentioning
confidence: 96%
“…These are important micronutrients involved in functional immune reconstitution. Their deficiency would therefore contribute to the worsening of the quantitative and qualitative deficit immunity [17][18][19][20][21][22][23].…”
Section: Immunologic and Clinical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in infected mice, selenium supplementation was able to decrease histological lesions by reducing inflammation [164][165][166][167][168]. [153,187,[201][202][203][204][205][206][207][208][209][210][211][212] No significant variation of Se level in infected people [213][214][215] Low selenium level associated with low CD4 count [153,203,206,207,211] Low selenium level associated with a higher progression to AIDS [201][202][203][204]206] Low selenium level associated with vaginal shedding of HIV [216] High selenium level associated with vaginal shedding of HIV [217] No significant variation of Se level in infected people treated with HAART [218] More skin desease in Se deficient HIV infected people [211] No…”
Section: Other Virusesmentioning
confidence: 99%
“…Many families have a well-defined immune deficiency due to compromised T-cell immunity or the keratinocyte-intrinsic immune system ( Biglari et al, 2024 ). In addition to genetically determined susceptibility to viral infections in patients with primary immune deficiency, many cases have been documented where the cutaneous lesions are associated with acquired immune deficiency, for example, secondary to acquired immune deficiency syndrome or human T-lymphotropic virus 1 (HTLV1) infections ( Akinboro et al, 2013 ; Cockerell, 1991 ; Valencia and Moreno, 2017 ).…”
Section: Introductionmentioning
confidence: 99%